The effect of the portfolio and other types of alternative assessments on ESP learners’ performance in essay writing - Hatim Kadhim, Shahad; M. Saalh, Shaima (International Journal of Psychosocial Rehabilitation, 2020)
This study aims at finding out the effect of the portfolio and other alternative assessments on Iraqi employees’ performance in essay writing. The participants are represented by 38 employees (27 females, 11 males) from different companies who joined the English language training course at Development and the Continuing Education Center University of Baghdad. They are divided into two equal groups: the experimental group (that has been taught according to the portfolio and alternative assessment techniques) and the control group (that has been taught according to the conventional method). The results show that the portfolio and other types of alternative assessments have significantly influenced the learners’ performance in essay writing and developed their performance. In light of the results, conclusions, recommendations, and suggestions have been set forward.